2021
DOI: 10.1161/str.0000000000000366
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Central Retinal Artery Occlusion: A Scientific Statement From the American Heart Association

Abstract: Purpose: Central retinal artery occlusion (CRAO) is a form of acute ischemic stroke that causes severe visual loss and is a harbinger of further cerebrovascular and cardiovascular events. There is a paucity of scientific information on the appropriate management of CRAO, with most strategies based on observational literature and expert opinion. In this scientific statement, we critically appraise the literature on CRAO and provide a framework within which to consider acute treatment and secondary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
139
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(192 citation statements)
references
References 73 publications
0
139
0
9
Order By: Relevance
“… 70 More than half of academic neurologists administer intravenous tPA to selected patients with acute CRAO based on observational data and in the lack of other efficient therapies. 71 There have been no adequate randomized clinical studies of intravenous tPA to date since earlier attempts were hampered by patient enrollment difficulties. Since the release of the meta-analysis of observational studies, intravenous tPA has been re-evaluated in four current cohorts with acute CRAO within 4.5 hours of onset.…”
Section: Can Hbot Be Used In Conjunction With Other Therapy Techniques To Enhance Its Effectiveness?mentioning
confidence: 99%
See 3 more Smart Citations
“… 70 More than half of academic neurologists administer intravenous tPA to selected patients with acute CRAO based on observational data and in the lack of other efficient therapies. 71 There have been no adequate randomized clinical studies of intravenous tPA to date since earlier attempts were hampered by patient enrollment difficulties. Since the release of the meta-analysis of observational studies, intravenous tPA has been re-evaluated in four current cohorts with acute CRAO within 4.5 hours of onset.…”
Section: Can Hbot Be Used In Conjunction With Other Therapy Techniques To Enhance Its Effectiveness?mentioning
confidence: 99%
“…Since the release of the meta-analysis of observational studies, intravenous tPA has been re-evaluated in four current cohorts with acute CRAO within 4.5 hours of onset. 71 A new meta-analysis that included these recent cohorts found that therapy within 4.5 hours had a considerable effect. 72 This analysis robustly repeated previous findings and served as the foundation for several ongoing clinical trials.…”
Section: Can Hbot Be Used In Conjunction With Other Therapy Techniques To Enhance Its Effectiveness?mentioning
confidence: 99%
See 2 more Smart Citations
“…A legfontosabb rizikófaktorok [9][10][11]: -azonos oldali a. carotis interna atherosclerosis, stenosis (a leggyakoribb kórok); -kardiológiai betegségek (patent foramen ovale, szívbillentyű-rendellenességek, ritmuszavar: a leggyakrabban pitvarfibrilláció); -a. carotis interna dissectio (nyaki trauma, Hornerszindróma); -gyulladásos (a leggyakrabban óriássejtes) arteritis; -hematológiai, hemosztazeológiai betegségek (veleszületett/szerzett); -septicus embolisatio; -iatrogén embolisatio (például orvosi diagnosztikus és szépészeti beavatkozások).…”
Section: Etiológiaunclassified